Phosphorus Nutrient Management through Synchronization of Application Methods and Rates in Wheat and Maize Crops - Rafiullah; Khan, Muhammad Jamal; Muhammad, Dost; Fahad, Shah; Adnan, Muhammad; Wahid, Fazli; Alamri, Saud; Khan, Farmanullah; Dawar, Khadim Muhammad; Irshad, Inam; Danish, Subhan; Arif, Muhammad; et al. (Plants (Basel, Switzerland), 2020)
Management of inorganic fertilizer is very important to obtain maximum crop yield and improved nutrient use efficiency in cereal crops. Fixation of phosphatic fertilizers in alkaline soils due to calcareousness is one of the major hurdles. It induces phosphorus nutritional stress that can decrease the yield of maize and wheat. Selection of a suitable application method and proper stage of crop for phosphorus (P) fertilizer has prime importance in better uptake of P and crop production. Among different application methods, soil and foliar application are widely adopted. In wheat and maize, knee height + tasseling and stem elongation + booting are critical stages towards P deficiency. That is why field trials were conducted to evaluate the supplemental effect of foliar P on maize and wheat yields. For that, 144 mM KH2PO4 was applied as foliar at knee height + tasseling and stem elongation + boot stages in maize and wheat, respectively. Soil application of 0, 20, 40 and 60 kg P ha-1 was done through broadcast and band methods. Results showed that foliar spray of 144 mM KH2PO4 at knee height + tasseling and stem elongation + boot stages in wheat and maize significantly enhanced grains yield and phosphorus use efficiency (PUE) where P was applied as banding or broadcast at the time of sowing. A significant decreasing trend in response to increasing soil P levels validated the efficacious role and suitability of foliar P. In conclusion, the use of P as foliar at knee height + tasseling and stem elongation + boot stages is an efficacious way to manage P fertilizer.
Keywords: grain yield; foliar application; nitrogen; calcareous soil; band application; phosphorus